IMF Research Bulletin, March 2013. (IMF Research Bulletin; IMF Research Bulletin ;, 2013)
The Research Summaries in the March 2013 Research Bulletinadiscuss "Trade Finance and Its Role in the Great Trade Collapse" (JaeBin Ahn) and "Sovereign Debt: How to Track Who Is Buying and Selling It" (Serkan Arslanalp and Takahiro Tsuda). The Q and A looks at "Seven Questions on the Implications of Global Supply Chains for Real Effective Exchange Rates" (Rudolfs Bems). Readers can also find in this issue aalisting of recent IMF Working Papers, Staff Discussion Notes, and Recommended Readings from IMF Publications. The Bulletin also includes a call for papers for a research conference and information onafree access to the IMF Economic Review in April.